Endoflife practices: The opinions of undergraduate medical students at a South African university - C Marais; J Smouse; G Poortier; A Fair; G Joubert; W J Steinberg (South African Journal of Bioethics and Law, 2017)
Background. Modern people live increasingly longer lives owing to advances in medicine and medical technology. This has raised many ethical questions regarding the prolongation of life, the right to die and euthanasia.Objective. To determine the opinions of medical students at the University of the Free State (UFS), South Africa (SA), regarding end-of-life practices: terminal pain management, withholding/withdrawing potentially life-sustaining treatment, advance directives and assisted dying.Methods. This was an observational, cross-sectional quantitative study. A self-administered and anonymous questionnaire was distributed to undergraduate medical students (preclinical and clinical). Demographic data were collected.Results. The overall response rate was 71.6% (481/672; preclinical 82.4% and clinical 64.4%). Students agreed that patients should have access to medical care (90.0%), and that pain medication should be state-supplied (86.3%). Students agreed that patients should have the right to refuse medical care (72.1%) and/or potentially life-preserving treatments (69.8%). Overall, 67.3% of students agreed that doctors should have the right to turn off life support if requested in the patient’s living will. Students (78.4%) disagreed that life support may be turned off without consent. Clinical students (54.5%) supported assisted dying being legal in SA, compared with the preclinical students (31.4%). While 43.0% of students agreed that assisted dying should be legal, only 36.2% were willing to perform the procedure themselves.Conclusion. Medical students at UFS agree with the legislation of three of the end-of-life practices: terminal pain management, withholding/withdrawing potentially life-sustaining treatment and advance directives. The clinical students, however, are more in favour than preclinical students of assisted dying becoming legal